SOCIO-ECONOMIC DETERMINATIONS THAT AFFECT THE INCOME OF TRADITIONAL FISHERMEN IN KRUENG MANE NORTH ACEH DISTRICT - Muttaqien; Wardiah; Muhammad Hafizh; Frengki Putra Ramansyah; Cut Zira Maulida (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Fishermen's income is the accumulation of fishermen's business results which do not stand alone, but are influenced by various factors. Therefore, fishermen's income includes capital, season, climate, fishing gear productivity, fishing area, fish price and number of fish caught. Fishermen's income factors include factors such as seasonal fluctuations, limited capital and human resources, access to exploitative fish trade networks, and the negative effects of fisheries modernization and the blue revolution, both of which have led to excessive depletion of marine resources. This process is still ongoing today, and fishermen are experiencing further impacts from a decline in their income levels and difficulties in obtaining their catch. The purpose of this research is to determine the income analysis method that calculates fixed costs and variable costs to income. Next, a production function analysis is carried out, where the production function describes the relationship between input and output. Based on this, it is hoped that the results of this research will be taken into consideration by the government in formulating policies related to the welfare of traditional fishermen with all their limitations. This type of research is descriptive quantitative with a research population of traditional fishermen in Krueng Mane, North Aceh. The type of data in this research uses primary data in the form of a questionnaire with a Likert scale where the research sample selection uses random sampling and then regression will be carried out using the SPSS application. The output of this research is the publication of international journals, indexed international proceedings and ISBN certified research reference books with TKT level 3, which is focused on proving the formulation of socio-economic factors that influence the income of traditional fishermen in Krueng Mane, North Aceh Regency.